Armochaetoglobins K–R, Anti‐HIV Pyrrole‐Based Cytochalasans from Chaetomium globosum TW1‐1. Issue 14 (30th March 2015) - Chen, Chunmei; Zhu, Hucheng; Wang, Jianping; Yang, Jing; Li, Xiao‐Nian; Wang, Jing; Chen, Keliang; Wang, Yanyan; Luo, Zengwei; Yao, Guangmin; Xue, Yongbo; Zhang, Yonghui
Abstract: Eight rare pyrrole‐based cytochalasans, termed armochaetoglobins K–R (1 –8 ), along with three known analogues (9 –11 ), were isolated from the solid culture broth of Chaetomium globosum TW1‐1, a symbiotic fungus derived from the medicinal terrestrial arthropod Armadillidium vulgare . Their structures were elucidated using a combination of spectroscopic analysis, a single‐crystal X‐ray diffraction experiment, and an electronic circular dichroism (ECD) calculation. Compounds4 –8 represent the first examples of chaetoglobosin‐type cytochalasans with an sp 3 methine carbon at C‐18. All of the isolates were evaluated for their anti‐HIV activities in vitro, and compounds2 –4, 7, 8, and10 showed significant anti‐HIV activities, with EC50 values ranging from 0.11 to 0.55 μM, and selectivity index (SI) values ranging from 12.33 to 75.42. A plausible biosynthetic pathway was proposed to explain the origin of the pyrrole ring. Abstract : Eight rare pyrrole‐based cytochalasans, armochaetoglobins K–R, were isolated from the solid culture broth of the fungus Chaetomium globosum, first isolated from the arthropod Armadillidium vulgare . Among them, armochaetoglobins L–N, Q, and R showed significant anti‐HIV activities, with EC50 values ranging from 0.25 to 0.55 µM, and selective index (SI) values ranging from 20.43 to 75.42.